A study on regression model using response surface methodology - Nooraziah A.; Tiagrajah V.J. (Trans Tech Publications Ltd, 2023)
Response Surface Methodology (RSM) mostly employs statistical regression method as it is practical, economical and relatively easy to use. The first and second order polynomial equation was developed using RSM. This polynomial model usually refers as a regression model. In this research, the objective is to find the best response surface method to model three factors and three levels parameters in machining. From the study, the Box-Behnken Design can develop a good regression model rather than Central Composite Design or Full Factorial Design. While, the second order regression model has proved to be more effective in predicting the performance of the given data set. © (2014) Trans Tech Publications, Switzerland.